PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP NILAI PELANGGAN SERTA DAMPAKNYA PADA LOYALITAS KONSUMEN (Survei Pada Konsumen Sepatu Converse All Star di Pontianak) - admin, Rio Ramadhan Putra B11110056 (Jurnal Manajemen Update, 2016)
This study aims to determine the effect of product quality and brand image to consumer loyalty through customer value as mediating variable. This research uses descriptive research design. The population in this study are consumers converse shoes all star in Pontianak, the minimum age of 17 years. Sampling using incidental sampling means as many as 100 people in Pontianak consumers. The data in this study using path analysis (Path Analysis) using SPSS 20. The results showed that the quality of the product (X1) and brand image (X2) significant effect on customer value (Y1). Brand image (X2) and customer value (Y1) significant effect on customer loyalty (Y2). Variable customer value (Y1) serves as a variable that mediates the effect of the variable quality of the product (X1) on consumer loyalty (Y2), but does not act as a mediating variable that influences the brand image variable (X2) on consumer loyalty (Y2).Keywords: product quality, brand image, customer value and customer loyalty.